Evaluation of the accuracy of measurements made at probable implant site using cone-beam computed tomography: A retrospective in vivo study - Hasan Sarfaraz; Mallika Shetty; K Harini; Sanath K Shetty; Sazia Amreen; Rachana Prabhu (Wolters Kluwer Medknow Publications, 2022)
Introduction: Computed Tomography (CT) was the most used 3D radiographic diagnostic technique for years, but cone-beam computed tomography (CBCT) was created to reduce radiation exposure, costs, and accessibility issues. Aim: To evaluate the accuracy of CBCT measurements made at probable implant sites. Materials and Methodology: This was a retrospective study that compared panoramic reconstructed CBCT with RVG measurements at 77 probable implant sites, especially mandibular posterior tooth-bounded edentulous areas. Measurements made were the mesiodistal width of the edentulous area at the crest and at the highest point of the adjacent tooth's contour and the length of the natural teeth in the mandibular first molar region from the highest cusp to the apex next to the edentulous area. Statistical analysis was done with the Statistical Package for the Social Sciences (SPSS) and the independent t-test. Results: The mean difference between CBCT and radiovisiography (RVG) readings for mesiodistal width at the crest and highest contour of the edentulous bounded two neighboring teeth was −0.21039 and 0.02961, respectively, which was not statistically significant. The mean difference between CBCT and RVG readings along the tooth was 0.80481, which was statistically significant (P = 0.018). RVG outperformed CBCT (SD = 1.7) in estimating tooth length. Conclusion: Conventional RVG radiographic measurements were similar to real tooth length, whereas CBCT panoramic reconstructions underestimated the lengths by 15% but were clinically acceptable. Clinical CBCT application requires operator abilities and knowledge with software. It is critical to pay close attention to the calibration of data obtained from clinical examination and CBCT.